Transpiration Response of Cotton to Vapor Pressure Deficit and Its Relationship With Stomatal Traits - Devi, Mura Jyostna; Reddy, Vangimalla R. (Frontiers in Plant Science, 2018)
Many studies have demonstrated that the cotton in warm environments is vulnerable to water-limitations thus reducing the yield. Limitation on maximum transpiration rate under high vapor pressure deficit (VPD), usually occurs during midday, is often considered as a water conservation trait. In the present study, seventeen cotton genotypes were studied for their transpiration rate (TR) response to various VPD environments. Out of seventeen, eight genotypes limited TR after approximately 2 kPa VPD and rest of them increased their TR with increased VPD. Five selected genotypes with different TR response to increasing VPD were further studied for gas exchange and stomatal properties. All genotypes, irrespective of exhibiting limited TR at high VPD, reduced stomatal conductance, photosynthesis and water potential at high VPD of 3.3 kPa. The genotypes with limited TR modified their stomatal traits mostly on the adaxial surface with frequent and small stomata under high VPD. The genotypes with limited TR also exhibited an increase in epidermal cell expansion and stomatal index at contrasting VPD gradients to effectively balance the liquid and vapor phase conductance to limit TR at high VPD.